Prognostic and predictive role of liquid biopsy in lung cancer patients - Goksel, Tuncay; Özgür, Su; Vardarlı, Aslı Tetik; Koç, Altuğ; Karakuş, Haydar Soydaner; Özdemir, Taha Reşid; Erdoğan, Kadri Murat; Aldağ, Ceyda; Veral, Ali; Komurcuoglu, Berna; Gursoy, Pınar; Arayici, Mehmet Emin; et al. (Frontiers in Oncology, 2024)
Lung cancer (LC) is a leading cause of cancer-related mortality worldwide. Approximately 80% of LC cases are of the non-small cell lung cancer (NSCLC) type, and approximately two-thirds of these cases are diagnosed in advanced stages. Only systemic treatment methods can be applied to patients in the advanced stages when there is no chance of surgical treatment. Identification of mutations that cause LC is of vital importance in determining appropriate treatment methods. New noninvasive methods are needed to repeat and monitor these molecular analyses. In this regard, liquid biopsy (LB) is the most promising method. This study aimed to determine the effectiveness of LB in detecting EGFR executive gene mutations that cause LC. One hundred forty-six patients in stages IIIB and IV diagnosed with nonsquamous cell non-small cell LC were included. Liquid biopsy was performed as a routine procedure in cases where no mutation was detected in solid tissue or in cases with progression after targeted therapy.Liquid biopsy samples were also obtained for the second time from 10 patients who showed progression under the applied treatment. Mutation analyses were performed using the Cobas ® EGFR Test, a real-time PCR test designed to detect mutations in exons 18, 20, and 21 and changes in exon 19 of the EGFR gene.Mutation positivity in paraffin blocks was 21.9%, whereas it was 32.2% in LB. Solids and LB were compatible in 16 patients. Additionally, while no mutation was found in solid tissue in the evaluation of 27 cases, it was detected in LB. It has been observed that new mutations can be detected not only at the time of diagnosis, but also in LB samples taken during the follow-up period, leading to the determination of targeted therapy. The results showed that "liquid biopsy" is a successful and alternative non-invasive method for detecting cancer-causing executive mutations, given the limitations of conventional biopsies.